2000
DOI: 10.1037/0735-7036.114.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and hand preference in chimpanzees (Pan troglodytes): Implications for pathological models of handedness in humans.

Abstract: The effect of birth order on hand preference was assessed in a sample of 154 captive-born chimpanzees. Subjects were classified as first, middle, or latter born using 2 classification criteria based on their birth order. Hand preference was measured using a task that elicited coordinated bimanual actions. Significant birth-order effects were found for both classification criteria, with firstand latter-born subjects exhibiting a lesser degree of right-handedness compared with middle-born subjects. These data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…With respect to birth order, the evidence of increased left-handedness among 1st and latter-born chimpanzees revealed in this study (which included more than 300 chimpanzees from two additional facilities) is consistent with previous results based on the YERKES chimpanzees alone (see Hopkins & Dahl, 2000). This suggests that the earlier observations are not restricted to the YERKES colony and generalize to at least two other colonies of apes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to birth order, the evidence of increased left-handedness among 1st and latter-born chimpanzees revealed in this study (which included more than 300 chimpanzees from two additional facilities) is consistent with previous results based on the YERKES chimpanzees alone (see Hopkins & Dahl, 2000). This suggests that the earlier observations are not restricted to the YERKES colony and generalize to at least two other colonies of apes.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, in previous research, we have found that there is a higher proportion of left-handedness among 1st and latter-born (parities >6) chimpanzees (Hopkins & Dahl, 2000). Moreover, we have previously found that concordance rates among maternal half-siblings are significantly higher when adjusted for the parity of the offspring.…”
Section: Introductionmentioning
confidence: 96%
“…Hopkins also attempts to demonstrate a genetic expression of handedness in chimpanzees, but discovers that there is not a significant relationship between handedness in the offspring and maternal or paternal handedness. A study of handedness and birth order indicated that in middle-born offspring there is significant heritability of handedness (Hopkins and Dahl, 2000: Hopkins, Dahl and Pilcher, 2000). The significance of these findings for cognitive evolution is yet unknown, but under close scientific scrutiny.…”
Section: Antecedents To Evolutionary Cognitive Neurosciencementioning
confidence: 99%
“…The genetic factors may play a role and this is supported by the observation that approximately 70% of individuals born to two left-handed parents are right-handed, which is significantly lower than the proportion of right-handed individuals born to two right-handed parents (McGee & Cozad, 1980;McManus & Bryden, 1992). Genetic explanations account for only part of the variances, however, leaving error or other factors to explain the remaining variability (Hopkins & Dahl, 2000). Most researchers agree that hand preference has a hereditary component, but not all agree as to the genetic mechanisms involved (reviewed in Levy, 1977).…”
Section: Handednessmentioning
confidence: 99%